Synthesis of ent‐Ketorfanol via a C–H Alkenylation/Torquoselective 6π Electrocyclization Cascade. Issue 41 (17th August 2015) - Phillips, Eric M.; Mesganaw, Tehetena; Patel, Ashay; Duttwyler, Simon; Mercado, Brandon Q.; Houk, Kendall N.; Ellman, Jonathan A.
Abstract The asymmetric synthesis of ent‐ketorfanol from simple and commercially available precursors is reported. A RhI‐catalyzed intramolecular CH alkenylation/torquoselective 6π electrocyclization cascade provides a fused bicyclic 1, 2‐dihydropyridine as a key intermediate. Computational studies were performed to understand the high torquoselectivity of the key 6π electrocyclization. The computational results demonstrate that a conformational effect is responsible for the observed selectivity. The ketone functionality and final ring are introduced in a single step by a redox‐neutral acid‐catalyzed rearrangement of a vicinal diol to give the requisite carbonyl, followed by intramolecular Friedel–Crafts alkylation.